Drospirenone promotes apoptosis in ectopic but inhibits proliferation in eutopic human endometrial stromal cells - Thanyarat Wongwananuruk; Somsin Petyim; Pawitra Suwannalert; Kittima Tungprasertpol; Supatra Klaymook (PLoS ONE, 2026)
Background Endometriosis is a complex gynecological condition characterized by endometrial tissue growing outside the uterus. In many in vitro studies, almost all progestins have indicated the anti-proliferation and apoptosis of endometriotic stromal cells. Drospirenone, a synthetic progestin structurally distinct from traditional progestins, still lacks sufficient data regarding its effects on endometriosis, particularly in terms of antiproliferative and pro-apoptotic activity. This study investigates the antiproliferative effects of drospirenone on eutopic (EU-ESCs) and ectopic human endometrial stromal cells (EC-ESCs), and compare its impact on apoptotic effects in both cell types. Methods and Findings In the study, paired EU-ESCs and EC-ESCs were obtained from patients diagnosed with endometriosis (n = 12). EU-ESCs and EC-ESCs were treated with and without drospirenone. Antiproliferative markers and apoptotic markers were evaluated and compared between the two groups. Interestingly, drospirenone at a concentration of 1 µM significantly affected cell viability in both EU-ESCs and EC-ESCs. In EU-ESCs, Ki-67 expression was significantly reduced compared to controls (0.17 vs. 1; p = 0.003), while in EC-ESCs, the reduction was not statistically significant. Caspase-3 expression was significantly increased in both EU-ESCs (1.13 vs. 1) and EC-ESCs (1.57 vs. 1) (p= 0.02 and p = 0.05, respectively). Additionally, BCL2 expression decreased in both cell types following treatment. BAX expression increased in both EU-ESCs and EC-ESCs. Expression levels of PTEN and P53 also increased in both cell types, with statistical significance observed only in EC-ESCs (p = 0.03 and p = 0.04, respectively). BAK expression decreased in EU-ESCs but increased in EC-ESCs compared to controls. Conclusions Drospirenone exhibits an antiproliferative effect on EU-ESCs and induces a more pronounced apoptotic response in EC-ESCs.